2021
DOI: 10.1002/slct.202102476
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Novel Polyethyleneimine Functionalized Polymeric Protic Ionic Liquids (PolyE‐ILs) with Protagonist Properties for Acid Catalysis

Abstract: Polyethyleneimine (PEI), a potent architecture backbone was explored for the synthesis of novel polymeric ionic liquids (PolyE-ILs) with protagonist properties. The simple quaternization of PEI dendrimer with Bronsted acids (H 2 SO 4 , H 3 PO 4 , CH 3 SO 3 H, CF 3 COOH and TsOH) leads to formation of series of protic PolyE-ILs with corresponding counter anions [HSO 4 ] À , [H 2 PO 4 ] À , [CH 3 SO 3 ] À , [CF 3 COO] À and [TsO] À. The physicochemical properties of synthesized PolyE-ILs were studied by using TG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Recently, Ukarde et al synthesized PolyE‐ILs with variable counter ions via a simple one‐pot neutralization reaction with PE using Brønsted acids such as H 2 SO 4 , H 3 PO 4 , CH 3 SO 3 H and TsOH to produce the corresponding PolyE‐ILs, i.e. [PEI] + [HSO 4 ] − , [PEI] + [H 2 PO 4 ] − , [PEI] + [CH 3 SO 3 ] − and [PEI] + [OTs] − , respectively 32 . In addition, [PEI] + [HSO 4 ] − showed excellent acidity in comparison with sulfuric acid, thus it can provide a potent substitute for sulfuric acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Ukarde et al synthesized PolyE‐ILs with variable counter ions via a simple one‐pot neutralization reaction with PE using Brønsted acids such as H 2 SO 4 , H 3 PO 4 , CH 3 SO 3 H and TsOH to produce the corresponding PolyE‐ILs, i.e. [PEI] + [HSO 4 ] − , [PEI] + [H 2 PO 4 ] − , [PEI] + [CH 3 SO 3 ] − and [PEI] + [OTs] − , respectively 32 . In addition, [PEI] + [HSO 4 ] − showed excellent acidity in comparison with sulfuric acid, thus it can provide a potent substitute for sulfuric acid.…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of [PEI] + [HSO 4 ] − was carried out in a fournecked round-bottom flask (RBF) along with the condenser, thermometer, addition funnel, vent, magnetic stirrer and heating plate, as reported previously. 32 A 1 g aliquot of polyethylenimine (PEI; 22.9 mmol of N on the basis of elemental analysis) and 2 g of deionized water were added to the RBF under stirring and an inert atmosphere. The solution was stirred for 15 min at room temperature (35 °C).…”
Section: General Process For Preparation Of [Pei] + [Hso 4 ] − Cataly...mentioning
confidence: 99%
See 1 more Smart Citation
“…The catalyst recycle and regeneration is an important and significant parameter for the process scale up and development of industrial catalyst. In the present process PolyE‐IL catalyst is homogenous and can be separated through membrane separation [35] . The operating temperature of the optimized process is 220 °C which is quite higher than the boiling point of MEK and water.…”
Section: Process Intensification Studymentioning
confidence: 99%
“…Concentration of nitrogen in the PEI will provide the range for sulphuric acid to be used for synthesis of PolyE‐IL‐1. It was observed that from elemental analysis PEI contains about 23mmoles of N/g of PEI [35] . Thus, the stoichiometric amount of Bronsted acid is required for complete neutralization of amine present on PEI backbone.…”
Section: Effect Of Counter Ion Concentrationmentioning
confidence: 99%